Progress of decreasing toxic polycyclic aromatic hydrocarbons content in coal-tar pitch by alkylation method - ZHANG Wenshuo; SHEN Jun; WANG Yugao; LIU Gang; LI Ruifeng; XU Qingbai (Meitan kexue jishu, 2023)
Coal-tar pitch (CTP) is a substance produced by ambient and/or vacuum distillation of high-temperature coal tar, although CTP has a large yield in China, however its wide application is limited due to its high toxicity. It was found that the toxicity of CTP was derived from its large amount of toxic Polycyclic Aromatic Hydrocarbons(PAHs) by 13C NMR and gas chromatography/mass spectrometer, including 16 PAHs monitored by the United States Environmental Protection Agency(EPA), such as fluoranthene、pyrene and benzo[a]pyrene. Various anti-toxic modification methods of CTP are introduced in the article, including chemical crosslinking method and physical chemistry method. The existing research mainly focuses on the former; by comparing the molecular structure of CTP and petroleum pitch, it is found that petroleum pitch has higher aliphatic hydrocarbons,it is proposed to add alkyl side chains to PAHs by alkylation of long-chain olefins to generate non-toxic long-chain alkyl substituted PAHs and inhibit the toxicity of CTP. Thus the method of alkylation cross-linking modification is focused on. The principle of the method and the catalysts used were summarized, the domestic and foreign related modification experiment results and theoretical research work were analyzed; Firstly, the alkylation of 16 kinds of PAHs with olefins was simulated by Gaussian, and the general rules of the reaction were obtained; Secondly, model compounds were selected for alkylation reaction, the possible reaction and its reaction mechanism of PAHs in the process of CTP modification were discussed; Finaly, the reaction conditions obtained from alkylation experiments of model compounds were applied to real CTP system, including 16 U.S. Environmental Protection Agency priority monitoring PAHs reduction in the modified coal tar pitch, as well as the changes of asphalt fume emissions and water soluble matter after modification in CTP, meanwhile the future research and application hot-spots and development of this method were prospected, it is hoped to provide reference for the environmental friendly utilization of CTP at home and abroad.